Molecular identification of somatostatin family in tilapia and the effect of food intake on pss2 and sstr3a - Ran Cai; Jiahui Zhang; Xiaozheng Yu; Yang Yu; Zongzhen Liao; Wensheng Li (Scientific Reports)
Abstract Somatostatin (SS) plays an important role in regulating food intake and following digestive functions of vertebrates mediated via somatostatin receptor (SSTR). However, the feedback regulation by which food intake regulate SS and SSTRs expression, and thereby their functions, remains poorly understood. Here, we cloned somatostatin genes (pss1, pss2 and pss3) and somatostatin receptors genes (sstr2a, sstr2b, sstr2c, sstr3a, sstr3b, sstr5a and sstr5b) from tilapia, Oreochromis niloticus and conducted their tissue distribution. Phylogenetic analysis and genomic synteny maps revealed their high homology across the vertebrates and evolution history. Following, synthesized SS-14 and SS-28 were both confirmed to bind to SSTRs and mediated Erk1/2 or Akt phosphorylation in a dose-dependent manner and time-course effect in 293T cell line as well as tilapia primary hepatocytes. It was observed that the expression levels of SS family showed dynamic change during food intake. In the early stages of feeding, pss2 expressed in gastric epithelium was down-regulated by food intake, and the following low pH after feeding reversed to up-regulate the pss2 mRNA level. This down and up dynamic change hinted that the first down pss2 prompted food digesting and the next up pss2 inhibited digestion, but it might need further explore to prove. Compared with it, sstr3a expression levels in submucosa up-regulated after feeding but did not display dynamic change. Our results contribute to the understanding of how somatostatin family respond to food intake during different stages of feeding, which provides basis for subsequent study of their function in gastrointestine of tilapia.